Geospatial mapping of public sentiment and infodemic on human papillomavirus vaccination in India: An indication to formulation of strategies for effective implementation - Priyobrat Rajkhowa; Cauvery Kalyanpur; Rakshitha K; Viola Savy Dsouza; Sanjay Pattanshetty; Prakash Narayanan; Kavitha Saravu; Helmut Brand (Taylor & Francis Group, 2024)
ABSTRACTThe implementation of Human Papillomavirus (HPV) vaccination is crucial for eliminating cervical cancer in India. The infodemic, characterised by misleading information, could hinder the successful implementation of the initiative. Misinformation related to the HPV vaccine, such as rumours, has been reported and circulated, contributing to an alarming pattern of vaccine hesitancy observed on social media. This study aimed to identify the public sentiment towards HPV vaccination based on the 'Behavioral and Social Drivers (BeSD)' framework through geospatial, content and sentiment analysis. A total of 1,487 tweets were extracted. After preprocessing, 1010 tweets were identified for sentiment and content analysis. The sentiments expressed towards the HPV vaccine are mixed, with a generally positive outlook on the vaccines. Within the population, there is a pervasive proliferation of misinformation, primarily focusing on vaccine safety and efficacy, contentious subjects, ethical considerations, and a prevalent sense of uncertainty in selecting the appropriate vaccine. These observations are crucial for developing targeted strategies to address public concerns and enhance vaccination rates. The insights gained from these results will guide policymakers, healthcare practitioners, and public health organisations to implement evidence-based interventions, thereby countering vaccine hesitancy and improving public health outcomes.